Italian survey on the residents’ surgical level in gynecology and obstetrics. : Italians do It Better? - Capozzi, Vito Andrea; Rosati, Andrea; Sozzi, Giulio; Armano, Giulia; Cianci, Stefano; Chiantera, Vito; Scambia, Giovanni; Berretta, Roberto; Frusca, Tiziana (Acta Biomedica Atenei Parmensis, 2020)
Purpose: The present study aims to investigate the number of surgical procedures performed by Italian residents and their confidence to carry out different surgeries in obstetrics and gynecology. Methods: The present study is a national survey including all Italian gynecology and obstetrics senior residents. A questionnaire including 25 questions was provided. The free Google Forms site was used to create the survey. The study was conducted from April to October 2019. The survey started from the University Hospital of Parma, a tertiary hospital, and was sent to all the Italian post-graduation medical school in gynecology and obstetrics. An e-mail was sent to all representative residents in gynecology and obstetrics in Italy, then forwarded to all the senior residents. Results: Of the 555 residents enrolled, 100 joined the survey (18.2%). The analysis of the different procedures performed by residents has shown that 53%, 57%, and 77% of the residents had never performed a laparotomic, laparoscopic, and vaginal hysterectomy, respectively. The analysis of cesarean section skills has shown that 1% of residents had never performed any simple cesarean section, and 6% of residents had never performed any complex cesarean section. Fifty-two doctors in training had never performed an operative vaginal delivery. Seventy-three and ninety-three residents performed more than thirty uterine curettages and sutures of 1st or 2nd degree tears, respectively. Conclusions: In Italy, senior residents are generally confident with the low-complexity procedures and also with complex cesarean sections. The number of Italian residents confident to perform a hysterectomy is poor.